Madagascar's EPI vaccine programs: A systematic review uncovering the role of a child's sex and other barriers to vaccination - Hahesy, Emma; Cruz-Espinoza, Ligia Maria; Nyirenda, Gabriel; Tadesse, Birkneh Tilahun; Kim, Jerome H.; Marks, Florian; Rakotozandrindrainy, Raphael; Wetzker, Wibke; Haselbeck, Andrea (Frontiers in Public Health, 2022)
Background Immunizations are one of the most effective tools a community can use to increase overall health and decrease the burden of vaccine-preventable diseases. Nevertheless, socioeconomic status, geographical location, education, and a child's sex have been identified as contributing to inequities in vaccine uptake in low- and middle-income countries (LMICs). Madagascar follows the World Health Organization's Extended Programme on Immunization (EPI) schedule, yet vaccine distribution remains highly inequitable throughout the country. This systematic review sought to understand the differences in EPI vaccine uptake between boys and girls in Madagascar. Methods A systematic literature search was conducted in August 2021 through MEDLINE, the Cochrane Library, Global Index Medicus, and Google Scholar to identify articles reporting sex-disaggregated vaccination rates in Malagasy children. Gray literature was also searched for relevant data. All peer-reviewed articles reporting sex-disaggregated data on childhood immunizations in Madagascar were eligible for inclusion. Risk of bias was assessed using a tool designed for use in systematic reviews. Data extraction was conducted with a pre-defined data extraction tool. Sex-disaggregated data were synthesized to understand the impact of a child's sex on vaccination status. Findings The systematic search identified 585 articles of which a total of three studies were included in the final data synthesis. One additional publication was included from the gray literature search. Data from included articles were heterogeneous and, overall, indicated similar vaccination rates in boys and girls. Three of the four articles reported slightly higher vaccination rates in girls than in boys. A meta-analysis was not conducted due to the heterogeneity of included data. Six additional barriers to immunization were identified: socioeconomic status, mother's education, geographic location, supply chain issues, father's education, number of children in the household, and media access. Interpretation The systematic review revealed the scarcity of available sex-stratified immunization data for Malagasy children. The evidence available was limited and heterogeneous, preventing researchers from conclusively confirming or denying differences in vaccine uptake based on sex. The low vaccination rates and additional barriers identified here indicate a need for increased focus on addressing the specific obstacles to vaccination in Madagascar. A more comprehensive assessment of sex-disaggregated vaccination status of Malagasy children and its relationship with such additional obstacles is recommended. Further investigation of potential differences in vaccination status will allow for the effective implementation of strategies to expand vaccine coverage in Madagascar equitably. Funding and registration AH, BT, FM, GN, and RR are supported by a grant from the Bill and Melinda Gates Foundation (grant number: OPP1205877). The review protocol is registered in the Prospective Register of Systematic Reviews (PROSPERO ID: CRD42021265000).